Glyphosate and AMPA occurrence in agricultural watershed: the case of Paraná Basin 3, Brazil - Mendonça, Cintia Franco Rodrigues [UNESP]; Boroski, Marcela; Cordeiro, Gilcélia Aparecido; Toci, Aline Theodoro (Taylor & Francis, 2020)
Glyphosate is the main herbicide used in soybean crops, and Brazil is one of the major soybean producers around the world. GLY and AMPA were evaluated in 124 surface waters samples of twenty one micro basins in Paraná Basin 3 (State of Parana, Brazil) over six subsequent weeks. A simple and economical routine methodology was established, based on lyophilization as a pre-concentration method. The validated method showed a limit of detection of 0.0125 and 0.025 µg L−1 for GLY and AMPA, respectively. In general, water samples presented concentrations ranging from 0.31 to 1.65 μg L−1 for GLY. Those values are below the maximum allowed amounts in Brazilian Law (65 μg L−1). The AMPA values were found in the range from 0.50 to 1.40 μg L−1. In summary, GLY was detected in 19.3% and it was quantified in 17.7% of the samples. AMPA was detected in 21.8% and it was quantified in 1.6% of the samples. Although samples did not present values higher than the established by Brazilian Law, GLY and AMPA appear constantly in the samples, which highlight the importance of monitoring studies in watersheds.
Keywords: AMPA; Brazil; Glyphosate; herbicide; lyophilization; Paraná Basin; pesticides; routine methodology; surface water; watersheds